Aural hematoma treatment using the button suture technique - Diana , Riya Ulfa; Andinata , Illona Christie (ARSHI Veterinary Letters, 2025)
Aural hematoma is a condition in which blood accumulates in the pinna and is characterized by fluid-filled swelling and erythema. One cause of aural hematoma is trauma, specifically an increased frequency of ear scratching and head shaking due to Otodectes cynotis ear mite infestation. Diagnostic tests in this case involved microscopic examination of ear cerumen, blood hematology, and blood biochemistry. The button suture technique is aimed at releasing the accumulated blood and preventing dead space in the pinna. Post-operative medication includes intramuscular injection of oxytetracycline and meloxicam, oral administration of albumin, administration ear drops (Sagestam®), and anti-mite treatment. The wound healing treatment was supported by a wound ointment (Digenta®) and the use of an Elizabethan collar. The patient’s condition gradually improved after surgery, and the patient was allowed to return home 30 days postoperatively.